2022
DOI: 10.1557/s43578-022-00644-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel Iron(III)-based MOF: Synthesis, characterization, biological, and antimicrobial activity study

Abstract: Recently infectious diseases and increasing microbial drug-resistant have caused many humorless health problems. To fill knowledge gaps and guide strategies at all levels for antimicrobials which represent a challenge and an urgent need. For these reasons, our target is developing a new effective antimicrobial drug with extended action time, multi-antimicrobial agents, low toxicity, and safe strategies. Metal–organic frameworks are promising materials for antimicrobial agents. Herein, a novel affordable Fe(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In addition, the antibacterial action of the ferric complex could also be related to the release of free ions in the solution that facilitates interaction between metal ions and bond. [56][57][58] Based on the strongest effect of the complex against gram positive bacteria as compared to gram negative bacteria, we suggest that our complex can affect the cell wall integrity of the microbial cell. This investigation was confirmed by the significant lysozyme activity against both gram positive cell wall from Micrococcus luteus and Staphylococcus aureus, with 27.99 UA/ml/min and 8.26 UA/ml/min, respectively.…”
Section: Antimicrobial Behavior Of the Fe(iii) Complexmentioning
confidence: 91%
“…In addition, the antibacterial action of the ferric complex could also be related to the release of free ions in the solution that facilitates interaction between metal ions and bond. [56][57][58] Based on the strongest effect of the complex against gram positive bacteria as compared to gram negative bacteria, we suggest that our complex can affect the cell wall integrity of the microbial cell. This investigation was confirmed by the significant lysozyme activity against both gram positive cell wall from Micrococcus luteus and Staphylococcus aureus, with 27.99 UA/ml/min and 8.26 UA/ml/min, respectively.…”
Section: Antimicrobial Behavior Of the Fe(iii) Complexmentioning
confidence: 91%
“…Their discovery showed that the rough surface of the MOF facilitated the efficient loading and release of primary fibroblast growth factors, promoting angiogenesis and collagen deposition. Bacterial infections, another challenging area of biomedicine, where studying metal-organic compounds begins to take a broader profile, were also partly addressed by Sheta et al [ 81 ]. Their research highlighted the ability of Fe(III)-MOF to inhibit the growth of bacteria, fungi, and yeasts, with excellent antimicrobial efficacy, at a concentration of 50 and 25 μg/mL Fe(III)-MOF.…”
Section: Exploring the Potential Of Mofs In Biomedical Applications B...mentioning
confidence: 99%
“… 43 As indicated by the above analysis, Fe-MOFs molecule exhibit high antibacterial activity against microorganisms, fungus, and yeast, as shown in Figure 13A and B . 162 , 163 MOFs containing bioactive links: For instance, it is obtained through the self-assembly of Fe 3+ ion and doxorubicin hydrochloride (DOX) molecule Fe-DOX@Gd-MOF, showing higher stability and controllable DOX release, as shown in Figure 13C . 139 Nevertheless, there has been scarce research in this category.…”
Section: Application Status Of Fe-mofs Materials In Medical Treatmentmentioning
confidence: 99%
“…Creative Commons. 163 ( C ) Synthesis of a mesoporous MIL-100(Fe) bacteria exoskeleton Reprinted from Permyakova A, Kakar A, Bachir J, et al In Situ Synthesis of a Mesoporous MIL-100(Fe) Bacteria Exoskeleton. ACS Materials Lett .…”
Section: Application Status Of Fe-mofs Materials In Medical Treatmentmentioning
confidence: 99%